PENGARUH TEKNIK SELF MANAGEMENT UNTUK MENURUNKAN PERILAKU MEROKOK SISWA KELAS IX SMP NEGERI 40 PEKANBARU MELALUI BIMBINGAN KELOMPOK - Irfan Satria; Syahrilfuddin Syahrilfuddin; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effects of self management techniques to reduce smoking behavior of class IX students of SMPNegeri 40 Pekanbaru through group guidance. This type of research is a quantitatiative study with an experimental metohod using the design on the one-group pretest – posttest design. The measuring instrument used in this study is a smoking behavior measurement scale consisting of 55 items before validation and after validation there are 47 item valid, with validity of 0.5255 and reliability of 0.918. Determination of the subject was obtained from the BK teacher’s recommendations and student case book data. The data analysis technique used is non-parametric statiscal techniques using the Wilcoxon test. The results of the study proved that the research hypothesis was accepted. This is known from